(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper is intended to investigate the status of ICT in the library of the Hindu College of Engineering in Sonipat. Several library programmes have been monitored and debated by their customers supporting information and communication technologies.